A structural study of Troger's base scaffold-based dyes for DSSC applications. (August 2017) - Urnikaite, Simona; Braukyla, Titas; Magomedov, Artiom; Kamarauskas, Egidijus; Malinauskas, Tadas; Getautis, Vytautas
Abstract: Three Troger's base scaffold-based metal-free sensitizersTD1, TD2 andTD3 with triphenylamine donor and rhodanine-3-acetic acid as an acceptor/anchoring group were designed and synthesized for dye-sensitized solar cells. The sensitizer series was designed to investigate the influence of the poly[n]enic (from n = 0 to 2) backbones and their anchoring effect in DSSCs. Optical, electrochemical and photovoltaic properties were compared with analogues dyesD1-D3 possessing one anchoring group. It has been proven that the extended polymethine chains ensure flexibility of these units and inspire the interaction between two chromophores promoting aggregate formation in these Troger's base-based dyes. Graphical abstract: Highlights: Novel D-π-A two-anchoring dyes based on Troger's base scaffold were synthesized. Two anchor groups are not always better than one. A poly[n]enic chain unit as π -linker inspires the interaction between two chromophores promoting aggregate formation. Photovoltaic performance can be influenced by π -linker length and number significantly.